The impact of organizational justice on the ethical leadership under the moderating influence of perceived support: A conceptual study - Halbusi, Hussam Al; Tehseen, Shehnaz *; Ramayah, T (Universiti Malaysia Sabah, 2017)
While a number of the researchers have conducted several studies on ethical leadership, however, not much is known about the role of organizational fairness in relationship to the ethical leadership behavior. This paper presented the proposed model in order to find out the perception of justice towards ethical leadership by using the two moderators namely perceived organizational support and perceived supervisor support. Thus, the proposition was made with respect to the impact of organizational justice on ethical leadership. It is also proposed that the perceived support such as organizational support and supervisor support could moderate the relationship between organizational justice and ethical leadership. The proposed model has been developed after reviewing the relevant existing studies and two underpinning theories namely social exchange theory and organizational support theory have been used to support the proposed model as well